Comprehensive review of hybrid aortic arch repair with focus on zone 0 TEVAR and our institutional experience - Singh, Saket; Pupovac, Stevan S.; Assi, Roland; Vallabhajosyula, Prashanth (Frontiers in Cardiovascular Medicine, 2022)
Even with increasing operator experience and a better understanding of the disease and the operation, intervention for aortic arch pathologies continues to struggle with relatively higher mortality, reintervention, and neurologic complications. The hybrid aortic arch repair was introduced to simplify the procedure and improve the outcome. With recent industry-driven advances, hybrid repairs are not only offered to poor surgical candidates but have become mainstream. This review discusses the evolution of hybrid repair, terminology pertinent to this technique, and results. In addition, we aim to provide a pervasive review of hybrid aortic arch repairs with reference to relevant literature for a detailed understanding. We have also discussed our institutional experience with hybrid repairs.